If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-6y + 9) + 4y = -13 Reorder the terms: 7(9 + -6y) + 4y = -13 (9 * 7 + -6y * 7) + 4y = -13 (63 + -42y) + 4y = -13 Combine like terms: -42y + 4y = -38y 63 + -38y = -13 Solving 63 + -38y = -13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + -38y = -13 + -63 Combine like terms: 63 + -63 = 0 0 + -38y = -13 + -63 -38y = -13 + -63 Combine like terms: -13 + -63 = -76 -38y = -76 Divide each side by '-38'. y = 2 Simplifying y = 2
| (x*x)+(x*x)=36 | | 137-4x=23x+23 | | 20.4-2c=5 | | 4x+y+1=-y-2x+3 | | (a-b)(a^2+2ab+b^2)= | | 12y^2+2y=0 | | (2c-d)(2c^2+2cd+d^2)= | | 7-7x=29-21x | | 3x+10+x+2=2x+20 | | -3x+7=28 | | 3x-45=6 | | 7(n+6)+8(n+4)= | | 8(x+3)+14(x+2)=74 | | 3(6z-1)-4(z+9)=4(z+1) | | 0.02-2.6=5.38 | | p=3a+5b | | 4x-12=x+6 | | 5b*6b= | | 3x*5x*2x= | | 6(2z-1)-2(z+3)=3(z+1) | | 20y-10=10 | | 3a*4a= | | b/14=5/10 | | X+(-4)+2x=14 | | 9-10x=77-38x | | -18x^2+65x+7=0 | | 3x^3-7x^2=-10 | | 9d-2d+6d-6=6d | | y/8=2/10 | | (3+5x^2)(3-5x^2)= | | 3x^3-7x^2=10 | | 9x-7=6x+16 |